1998
DOI: 10.1007/s002449900294
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Total Mercury and Methyl Mercury in Water, Sediment, and Fish from South Florida Estuaries

Abstract: Concentrations of total mercury and methyl mercury were determined in sediment and fish collected from estuarine waters of Florida to understand their distribution and partitioning. Total mercury concentrations in sediments ranged from 1 to 219 ng/g dry wt. Methyl mercury accounted for, on average, 0.77% of total mercury in sediment. Methyl mercury concentrations were not correlated with total mercury or organic carbon content in sediments. The concentrations of total mercury in fish muscle were between 0.03 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
114
2
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(132 citation statements)
references
References 34 publications
12
114
2
1
Order By: Relevance
“…This value was more than five times the 30 ”g of Hg per day maximum intake concentration established by the World Health Organization (WHO). Results of this magnitude have already limited the human consumption of piscivorous species in the USA (Kannan et al, 1998) and Australia (Simpfendorfer and Donohue, 1998). Higher Hg concentration in apex predator fish species is recognizably a problem associated with the biomagnification process Marcovecchio et al (1991).…”
Section: Resultsmentioning
confidence: 99%
“…This value was more than five times the 30 ”g of Hg per day maximum intake concentration established by the World Health Organization (WHO). Results of this magnitude have already limited the human consumption of piscivorous species in the USA (Kannan et al, 1998) and Australia (Simpfendorfer and Donohue, 1998). Higher Hg concentration in apex predator fish species is recognizably a problem associated with the biomagnification process Marcovecchio et al (1991).…”
Section: Resultsmentioning
confidence: 99%
“…The hazard index was calculated according to Kannan et al (1998) using the reference dose (RfD) for THg (0.3 ”g/kg body weight per day) set forth by US EPA.…”
Section: Methodsmentioning
confidence: 99%
“…Potential health hazard caused by mercury in fish was calculated according to the method of Kannan et al (1998), who described the calculation of the hazard index associated with fish consumption. The hazard indexes calculated for Hg are given in Table 3.…”
Section: Health Hazard Assessmentmentioning
confidence: 99%
“…The normalization was performed since studies have shown predictable associations of lipophilic contaminants as well as MeHg with detrital carbon (Castro and Vale 1995;King et al 2001;Nhan et al 2001). However, other studies from the southeast have shown the relationship between Hg and carbon content to be complex (Kannan et al 1998b), most likely because carbon is only one component that can influence methylation processes.…”
Section: Home Rangementioning
confidence: 99%